Nonspecific immune responses and mechanisms of resistance to Eimeria papillata infections in mice. - Schito, M L (1997)
Severe combined immunodeficient (SCID)-beige mice inoculated with the intracellular parasite Eimeria papillata produced significantly more oocysts during primary infections than inoculated immunodeficient SCID mice. Therefore, the addition of the beige mutation, which detrimentally affects neutrophil and natural killer (NK) cell functions, enhanced the parasites' ability to reproduce within the small intestine. To identify which of these two cell types is responsible for a protective immune response during primary infection, the following groups of mice were inoculated: (i) SCID mice depleted of neutrophils with antigranulocyte monoclonal antibody (RB6-8C5), (ii) C57BL/6 mice depleted of NK cells with the anti-NK-1.1 monoclonal antibody (PK136), and (iii) transgenic Tg epsilon26++ mice (T and NK cell deficient). To identify the mechanisms of immunity during primary and secondary infections, gamma interferon (IFN-gamma) knockout and perforin knockout mice were inoculated. Oocyst output was found to be significantly higher during primary infection for mice depleted of NK cells by administration of anti-NK-1.1 antibodies, for Tg epsilon26++ mice, and for IFN-gamma knockout mice. During secondary infections, only perforin knockout mice produced significantly more oocysts compared to control mice. Our observations suggest that NK cells inhibit E. papillata oocyst output during primary infection by the production of IFN-gamma and that this inhibition is independent of perforin. Immunity to reinfection does not require IFN-gamma but appears to be mediated, at least in part, by a perforin-dependent mechanism.